Homeschooling Reconsidered - Dwyer, James (Philosophical Inquiry in Education)

(untitled) (Canadian Philosophy of Education Society, 2022)
Homeschooling was occasionally a subject of popular interest pre-COVID, when media reported horrific cases of child abuse under the guise of homeschooling, or when controversies erupted over efforts in state legislatures or local school boards to introduce very modest oversight measures. COVID made homeschooling something nearly every parent considered as a long-term educational option for their children, and something arguably – depending on one’s definition of homeschooling – nearly all experienced. This article extracts from the societal experience of forced remote learning, challenging theoretical questions about the distinction between homeschooling and “regular schooling”; the wisdom of traditional brick-and-mortar, multi-service schooling; and the appropriateness of state officials passing judgement on any private form of schooling.